Effectiveness of One-Year Pemafibrate Therapy on Non-Alcoholic Fatty Liver Disease Refractory to Long-Term Sodium Glucose Cotransporter-2 Inhibitor Therapy: A Pilot Study - Satoshi Shinozaki; Toshiyuki Tahara; Kouichi Miura; Alan Kawarai Lefor; Hironori Yamamoto (Life, 2023)
Background: Both pemafibrate and sodium glucose cotransporter-2 (SGLT2) inhibitor can decrease serum transaminase levels in patients with non-alcoholic fatty liver disease (NAFLD) complicated with dyslipidemia and type 2 diabetes mellitus (T2DM), respectively. However, the effectiveness of combined therapy has been rarely reported. Methods: This is a two-center retrospective observational study. NAFLD patients complicated with T2DM treated with pemafibrate for >1 year were included, in whom prior treatment with SGLT2 inhibitor > 1 year failed to normalize serum alanine aminotransferase (ALT) levels. Hepatic inflammation, function, and fibrosis were assessed by ALT, albumin-bilirubin (ALBI) score, and Mac-2 binding protein glycosylation isomer (M2BPGi) levels, respectively. Results: Seven patients were included. The median duration of prior treatment with SGLT2 inhibitors was 2.3 years. During the one year before starting pemafibrate therapy, the therapy did not significantly change hepatic enzymes. All patients received pemafibrate 0.1 mg twice daily without dose escalations. During one year of pemafibrate therapy, triglyceride, aspartate aminotransferase, ALT, γ-glutamyl transpeptidase, ALBI score, and M2BPGi levels significantly improved (p < 0.05), although weight or hemoglobin A1c did not significantly change. Conclusions: One year of pemafibrate therapy improves markers of hepatic inflammation, function, and fibrosis in NAFLD patients in whom long-term SGLT2 inhibitor therapy failed to normalize serum ALT.